Leadership in colonial Africa : disruption of traditional frameworks and patterns - Jallow, Baba Galleh (Palgrave studies in African leadership., 2014)
Taken together, the chapters in this book represent a tapestry of leadership frameworks and cultures in colonial Africa. Scholars across disciplines explore the nature and evolution of leadership born of the colonial encounter between white colonialists and native Africans as well as the leadership that ultimately led to independence. Leadership in Colonial Africa highlights colonial disruptions of traditional leadership patterns in Africa and how African leaders, traditional and nationalist, reacted to these disruptions. Jallow examines the emergence of modern leadership cultures in Africa and argues that leadership studies theory may usefully be deployed in the study of African leadership.